Directing-Group-Assisted Transition-Metal-Catalyzed Selective BH Functionalization of o-Carboranes - Zhang, Jie; Xie, Zuowei (Synthesis, 2024)
Carboranes are a type of molecular clusters consisting of carbon, hydrogen, and boron atoms. They possess unique characteristics, such as three-dimensional aromaticity, icosahedral geometry, and robustness. Functionalized carboranes have been utilized in various fields, including medicine, materials, and organometallic/coordination chemistry. In this context, selective functionalization of o-carboranes has received tremendous attention, specifically in the regio- and enantioselective modification of the ten chemically similar BH vertices within the carborane cage. In recent years, significant progress has been made in catalytic vertex-specific BH functionalization, as well as achieving enantioselective functionalization of the cage BH. This review provides an overview of the recent advancements in this research field.1 Introduction2 Carboxy-Assisted BH Functionalization2.1 Formation of B–C Bonds2.2 Formation of B–N Bonds2.3 Formation of B–O Bonds2.4 Formation of B–X Bonds2.5 Consecutive Formation of B–C and B–Y (Y = N, O) Bonds3 N-Based Directing-Group-Assisted B–H Functionalization3.1 Acylamino as a Directing Group3.2 Amide as a Directing Group3.3 Pyridyl as a Directing Group3.4 Imine as a Directing Group4 Phosphinyl-Assisted Cage B–H Functionalization5 Bidentate-Directing-Group-Assisted B–H Functionalization6 Other Directing-Group-Assisted B–H Functionalization7 Conclusions
Keywords: BH functionalization; directing groups; transition metals; catalysis; o-carboranes